Hepatic involvement as an initial manifestation of multiple myeloma: a case report with atypical imaging features - Pu, Zongsheng; Zhan, Lujiang; Zha, Yimi; Li, Yilin; Qiu, Shilin; He, Yinfu; Yang, Yanhong; Feng, Zaihui; Zhu, Xingxing (Frontiers in Oncology, 2025)
Hepatic involvement as the initial manifestation of multiple myeloma (MM) is exceedingly rare and presents significant diagnostic challenges due to its heterogeneous imaging features, which often mimic metastatic liver tumors. We report a case of a 62-year-old man presenting with right upper quadrant discomfort. Imaging revealed a hypoechoic lesion in segment II of the liver on ultrasound, a low-density area with mild enhancement on contrast-enhanced CT, and atypical MRI features including hyperintensity on T1- and T2-weighted images, mild diffusion restriction on diffusion-weighted imaging (DWI), and minimal enhancement post-Gd-DTPA administration. Histopathology demonstrated diffuse infiltration of atypical plasma cells consistent with plasmacytoma, supported by immunohistochemical positivity for CD138, CD38, MUM1, and CD56, and an elevated serum β2-microglobulin level, confirming the diagnosis of MM with hepatic involvement. This case underscores the variability of extramedullary myeloma (EM) imaging presentations in the liver and highlights the importance of including EM in the differential diagnosis of atypical hepatic lesions, especially when accompanied by osteolytic bone lesions or abnormal serum markers. Histopathological confirmation remains essential for definitive diagnosis and guiding treatment.